Severe 25‐hydroxyvitamin D deficiency identifies a poor prognosis in patients with hepatocellular carcinoma – a prospective cohort study. Issue 10 (29th March 2014) - Finkelmeier, F.; Kronenberger, B.; Köberle, V.; Bojunga, J.; Zeuzem, S.; Trojan, J.; Piiper, A.; Waidmann, O.
Summary Background Vitamin D is involved in many biological processes. The role of vitamin D in patients with hepatocellular carcinoma (HCC) remains inconclusive, although there is evolving evidence that vitamin D may modulate cancer development and progression. Aim To evaluate serum vitamin D as prognostic parameter in HCC, we performed a prospective cohort study. Methods HCC patients were prospectively recruited and 25‐hydroxyvitamin D3 (25(OH)D3) levels were determined. 25(OH)D3 levels were compared to stages of cirrhosis and HCC stages with nonparametric Kruskal–Wallis tests and Spearman correlations in 200 HCC patients. The association of the 25(OH)D3 levels and overall survival (OS) was assessed in uni‐ and multivariate Cox regression models. Results Two‐hundred patients with HCC were included. The mean follow‐up time was 322 ± 342 days with a range of 1–1508 days. Nineteen patients underwent liver transplantation and 60 patients died within the observation time. The mean serum 25(OH)D3 concentration was 17 ± 13 ng/mL with a range of 1–72 ng/mL. 25(OH)D3 serum levels negatively correlated with the stage of cirrhosis as well as with stages of HCC. Patients with severe 25(OH)D3 deficiency had the highest mortality risk (hazard ratio 2.225, 95% confidence interval 1.331–3.719, P = 0.002). Furthermore, very low 25(OH)D3 levels were associated with mortality independently from the MELD score and high alpha‐Fetoprotein levels (>400 ng/mL) in a multivariate Cox regression model. Conclusions We conclude that 25(OH)D3 deficiency is associated with advanced stages of hepatocellular carcinoma and it is a prognostic indicator for a poor outcome.